Legal Aspects of Business Dispute Resolution through Alternative Out-of-Court Settlements - Manopo, Jusril D.; G. Baharu, Wiranto (Estudiante Law Journal, 2025)
Legal aspects in business dispute resolution through alternative dispute resolution (ADR) play an essential role as they offer a more efficient, flexible, and lower-cost solution compared to litigation processes in court. Various ADR methods, such as mediation, arbitration, and negotiation, are governed by legal regulations aimed at ensuring fairness for all parties involved. Key legal aspects of ADR in Indonesia include the legal foundations in the Civil Code, Law No. 30 of 1999 on Arbitration and Alternative Dispute Resolution, and other related regulations. Mediation and arbitration have become preferred choices for business dispute resolution due to their time and cost efficiency, as well as their ability to preserve relationships between the parties involved. However, challenges in its implementation, such as the lack of public awareness, inconsistent application of legal provisions, and limited professional capacity of mediators or arbitrators, continue to hinder the optimal utilization of ADR mechanisms. Furthermore, the enforceability of ADR outcomes particularly arbitral awards often faces procedural barriers and resistance from parties unfamiliar with non-litigation solutions. Despite these obstacles, the development of ADR in Indonesia continues to show promise, supported by judicial encouragement and increasing inclusion in contractual clauses. In conclusion, strengthening the legal framework, enhancing professional standards, and promoting ADR literacy among stakeholders are crucial steps in advancing effective business dispute resolution outside the courtroom.